Project Based Learning (PBL) to Improve Listening Skills in Arabic Language Learning - Binti Musyarofah; Nur Halifah; Sisran Sisran; Yeni Nuriah Fitri (Nurul Jadid University, 2025)
This study aims to describe the implementation of the Project-Based Learning (PBL) model in improving listening skills (maharah istima’) among students of the Arabic Language Development Program (PKPBA) at UIN Maulana Malik Ibrahim Malang. Using a qualitative descriptive approach, data were collected through observation, interviews, and documentation. The findings reveal that the PBL model effectively fosters students’ active participation, motivation, and comprehension in Arabic listening activities. The learning process was carried out through systematic stages—listening to audio materials, repetition, interactive questioning, project creation, and presentation—which transformed the class atmosphere from passive listening to active, communicative engagement. The integration of the PBL model with the audiolingual approach strengthened students’ ability to comprehend Arabic sounds, vocabulary, and contextual meanings. In addition to cognitive gains, students demonstrated higher confidence, creativity, and collaboration when completing group video projects. Theoretically, this study supports the constructivist and humanistic learning perspectives that emphasize meaningful learning through experience and interaction. Practically, it provides insights for Arabic language educators to apply PBL as an effective pedagogical strategy for enhancing listening comprehension in higher education